Neighborhood Success Stories : Creating and Sustaining Affordable Housing in New York - Lamberg, Carol (Book collections on Project MUSE., 2018)
This book illustrates examples of successful community development on the Lower East Side of Manhattan and in the Bronx, using seven different methods of finance, only one of which is still available today. The buildings were developed between 1975 and 1997.